2016
DOI: 10.1002/art.39491
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Porphyromonas gingivalis Indicate Interaction Between Oral Infection, Smoking, and Risk Genes in Rheumatoid Arthritis Etiology

Abstract: Objectives To investigate the role of the periodontal pathogen Porphyromonas gingivalis in rheumatoid arthritis (RA) etiology, we have analysed the antibody response to P. gingivalis virulence factor arginine gingipainB (RgpB) in relation to anti-citrullinated protein antibodies (ACPA), smoking and HLA-DRB1 shared epitope (SE) alleles, in patients with periodontitis (PD) and RA, and in controls. Methods Anti-RgpB IgG was measured by ELISA in 65 PD patients and 59 non-PD controls, and in 1,975 RA cases and 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 59 publications
(84 reference statements)
8
85
2
5
Order By: Relevance
“…Oral ulcers in the setting of SLE have long been considered to be predictors of systemic vasculitis and worse prognosis. 42 As mentioned above, oral and nasal ulcers are considered as clinical criterion for SLE in the SLICC classification system. 25,30,40 To date, oral ulcers have not been associated with nephritis, 24,25 with vasculitis 24,25,40 or with a significant change in serum levels of anti-dsDNA antibodies, ANA or complement.…”
Section: Discussionmentioning
confidence: 99%
“…Oral ulcers in the setting of SLE have long been considered to be predictors of systemic vasculitis and worse prognosis. 42 As mentioned above, oral and nasal ulcers are considered as clinical criterion for SLE in the SLICC classification system. 25,30,40 To date, oral ulcers have not been associated with nephritis, 24,25 with vasculitis 24,25,40 or with a significant change in serum levels of anti-dsDNA antibodies, ANA or complement.…”
Section: Discussionmentioning
confidence: 99%
“…We have circumvented this problem by generating an I-A°/I-E° mouse on the C57BL/6 background that expresses a chimeric mouse/human RA susceptibility allele HLA-DR1(*0101) as a transgene. Recent research has suggested that this same DR1 restriction element may also serve as a susceptibility allele for periodontal disease [24, 25], providing a unique opportunity for use as an animal model that is perfectly suited for the analysis of linkages between the two disease processes. While there has been one study in which HLA-DR4 tg mice were used to look at the role of citrullinated human α-enolase [11], to our knowledge no HLA-DR1 mice have been challenged with P. gingivalis to assess its role in ACPA development or modulation of arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…При РА обнаружен феномен аутоцитруллинирования ПАД P. gingivalis, ведущий к образованию антител к ПАД [149], который, однако, не характерен для «преклиниче-ской» фазы РА [150]. В то же время данные эпидемиологи-ческих исследований не подтверждают связь между пе-риодонтитом и РА [151], хотя антитела, специфичные к P. gingivalis, обнаруживаются в сыворотках АЦБ-пози-тивных пациентов с РА [152]. Более того, недавно было показано, что у млекопитающих кальций-зависимая ПАД цитруллинирует специфические аргининовые остатки внутри полипептидной цепи молекулы белка (эндоцит-руллинирование), в то время как ПАД P. gingivalis модифи-цирует только С-терминальный аргинин [153].…”
Section: фак торы внешней средыunclassified